2019
DOI: 10.1007/s00420-019-01457-w
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort glare and psychological stress during computer work: subjective responses and associations between neck pain and trapezius muscle blood flow

Abstract: Exposure to additional environmental stress during computer work, such as visual and psychological demands, is associated with increased eye and neck discomfort, altered moods, and reduced well-being. The aim of this study is to elucidate further how subjective responses in healthy, young females with normal binocular vision are affected by glare and psychological stress during computer work, and to investigate possible associations between trapezius muscle blood flow and neck pain development. Methods Forty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 95 publications
0
24
0
2
Order By: Relevance
“…Stress is related to pain and disability [ 14 , 15 ]. Perceived stress is a risk factor for neck pain [ 19 , 22 ]. At least two investigations, with fair methodological quality, have found that adolescents with neck pain had significantly more symptoms of stress than adolescents without neck pain, and that permanent and/or regular feelings of stress was significantly associated with an increased odds of reporting neck pain [ 23 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress is related to pain and disability [ 14 , 15 ]. Perceived stress is a risk factor for neck pain [ 19 , 22 ]. At least two investigations, with fair methodological quality, have found that adolescents with neck pain had significantly more symptoms of stress than adolescents without neck pain, and that permanent and/or regular feelings of stress was significantly associated with an increased odds of reporting neck pain [ 23 ].…”
Section: Main Textmentioning
confidence: 99%
“…There is some evidence that high skill discretion has a protective effect from neck pain [ 2 ]. However, working with a computer is considered to be an occupational condition that causes neck pain [ 19 ]. Several factors have been suggested to play key roles in the development of computer-related neck pain, including posture, duration working at a computer, psychological stress, repetitive movements, prolonged static loads, and the psychosocial effects of the working environment [ 19 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4]106 Discomfort glare has also been linked with adverse effects on mood and wellbeing. 107 Notwithstanding that discomfort glare varies within the same space depending on the position and direction of view, 108 there are also significant individual differences in sensitivity. Some people may be unaware of, or undisturbed by, glaring lighting, whilst others in the same space may experience discomfort symptoms.…”
Section: Glarementioning
confidence: 99%
“…It is essential to know the risk factors associated with NBP in order to prevent it, with the aim of reducing the serious socioeconomic repercussions caused by NBP [ 8 ]. This condition presents a multifactorial approach: sedentary lifestyle [ 9 ], obesity [ 10 ], lack of muscle strength [ 11 , 12 ], lack of flexibility [ 13 ] and psychosocial [ 14 , 15 ] and work-related factors [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%